Arbuscular Mycorrhizal Fungi Selectively Promoted the Growth of Three Ecological Restoration Plants - Hengkang Xu; Yuchuan Shi; Chao Chen; Zhuo Pang; Guofang Zhang; Weiwei Zhang; Haiming Kan (Plants, 2024)
Arbuscular mycorrhizal inoculation can promote plant growth, but specific research on the difference in the symbiosis effect of arbuscular mycorrhizal fungi and plant combination is not yet in-depth. Therefore, this study selected Medicago sativa L., Bromus inermis Leyss, and Festuca arundinacea Schreb., which were commonly used for restoring degraded land in China to inoculate with three AMF separately, to explore the effects of different AMF inoculation on the growth performance and nutrient absorption of different plants and to provide a scientific basis for the research and development of the combination of mycorrhiza and plants. We set up four treatments with inoculation Entrophospora etunicata (EE), Funneliformis mosseae (FM), Rhizophagus intraradices (RI), and non-inoculation. The main research findings are as follows: the three AMF formed a good symbiotic relationship with the three grassland plants, with RI and FM having more significant inoculation effects on plant height, biomass, and tiller number. Compared with C, the aboveground biomass of Medicago sativa L., Bromus inermis Leyss, and Festuca arundinacea Schreb. inoculated with AMF increased by 101.30–174.29%, 51.67–74.14%, and 110.67–174.67%. AMF inoculation enhanced the plant uptake of N, P, and K, and plant P and K contents were significantly correlated with plant biomass. PLS-PM analyses of three plants all showed that AMF inoculation increased plant nutrient uptake and then increased aboveground biomass and underground biomass by increasing plant height and root tillering. This study showed that RI was a more suitable AMF for combination with grassland degradation restoration grass species and proposed the potential mechanism of AMF–plant symbiosis to increase yield.